2016
DOI: 10.1103/physrevb.94.035437
|View full text |Cite
|
Sign up to set email alerts
|

Excitons and optical spectra of phosphorene nanoribbons

Abstract: On the basis of many-body ab-initio calculations, using single-shot G0W0 method and BetheSalpeter equation, we study phosphorene nanoribbons (PNRs) in the two typical zigzag and armchair directions. The electronic structure, optical absorption, electron-hole (exciton) binding energy, exciton exchange splitting, and exciton wave functions are calculated for different size of PNRs. The typically strong splitting between singlet and triplet excitonic states make PNRs favorable systems for application in optoelect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 50 publications
6
37
0
Order By: Relevance
“…This is also consistent with the presence of stronger quantum confinement effects in hydrogenpassivated PNRs of ZZ-1 edge as compared to AC edge. 2023,2529 By “stronger” it is meant that for a given NR width the PAGE quantum-confinement-induced increase in the band gap is larger, at least in the range of widths considered. Also, the band gap values decay away from the edge when the supercell size and radius dimensions result in a sizable “bulk” region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also consistent with the presence of stronger quantum confinement effects in hydrogenpassivated PNRs of ZZ-1 edge as compared to AC edge. 2023,2529 By “stronger” it is meant that for a given NR width the PAGE quantum-confinement-induced increase in the band gap is larger, at least in the range of widths considered. Also, the band gap values decay away from the edge when the supercell size and radius dimensions result in a sizable “bulk” region.…”
Section: Resultsmentioning
confidence: 99%
“…For hydrogen-passivated AC and ZZ-1 PNRs it was found that with decreasing width the electronic band gap, optical band gap, and exciton binding energies all increase ( i.e ., the quantities all follow the quantum confinement trends). 29 Since an antidot lattice is closely related to a network of curved NRs, it is reasonable to assume that the scaling of the optoelectronic properties with the geometric features in the PNRs and the PALs will be similar. Furthermore, it is expected that the spatial distribution of the optical band gap in the PALs will also be bimodal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the PNR edge structures, they are elementarily classified into two types, namely armchair PNRs (aPNRs) and zigzag PNRs (zPNRs). It has recently been shown by us that the charge distributions around the gap in aPNRs are localized in the middle of the nanoribbons, while in zPNRs they are mostly distributed in the width of the ribbons [10]. Consequently, physical properties of zPNRs are very sensitive to the width, structural defects, and edge morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Electron-beam sculpting produces nanoscale constrictions over limited (< 15 nm) lengths rather than isolated nanoribbons 16 . Alternatively, e-beam lithography has, to date, only produced ribbons with minimum widths of ~60 nm and heights of ~3 nm (Ref 25) meaning their band gaps and electronic properties are close to those of bulk BP 2,3,14,20,22 . Such lithography also relies on first exfoliating and then crystallographically aligning BP, limiting the scalability essential for many applications.…”
mentioning
confidence: 99%